Roteiro geoturístico na Ilha de Mosqueiro Belém/Pa: instrumento para a valoração e divulgação da geodiversidade local - SILVA, Nailton Nascimento da (2022)
Geodiversity refers to the abiotic aspects of the landscape, which can present values from a scientific, cultural, tourist and economic point of view. In this way, geotourism routes emerge as fundamental instruments for the dissemination, conservation and valuation of physical-natural formations, and can contribute to the development of various actions and activities, among them the conservation of local Geodiversity. It is important to highlight that Geodiversity is of paramount importance for tourism on the island, as the most frequented beaches are the ones that have the largest number of physical elements of nature, confirming the geotourism potential present on the Island of Mosqueiro. Due to the fact that the Island has an already consolidated tourist potential and a variety of geodiversity elements, a Geotourism Roadmap was elaborated. Thus, the objective of this research is to highlight the script as an instrument for the valuation and dissemination of knowledge about Geodiversity and collaborating for the implementation of Geoconservation in the municipality of study. The methodological procedures adopted in this research were divided into two stages, namely: Bibliographic Survey and Fieldwork. The results obtained with the research reveal that the Geotourism Route on Mosqueiro Island is an extremely important tool for the dissemination, conservation and valuation of local Geodiversity, thus being able to contribute to the development of several actions, among them the awareness of the population and environmental education.